2014
DOI: 10.1016/j.jfoodeng.2014.05.025
|View full text |Cite
|
Sign up to set email alerts
|

Formulation engineering of water in cocoa – Butter emulsion

Abstract: Where a licence is displayed above, please note the terms and conditions of the licence govern your use of this document. When citing, please reference the published version. Take down policy While the University of Birmingham exercises care and attention in making items available there are rare occasions when an item has been uploaded in error or has been deemed to be commercially or otherwise sensitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 45 publications
2
13
0
Order By: Relevance
“…Depending on φ and on dropletscontinuous phase interactions, emulsion viscosity is higher than the viscosity of the pure continuous phase which may affect processability. The potential of confectionery emulsifiers to modulate rheological properties of dispersions has been shown for solid/liquid systems such as chocolate, and for liquid/liquid systems (Chevalley, 1999;Schantz & Rohm, 2005;Sullo et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Depending on φ and on dropletscontinuous phase interactions, emulsion viscosity is higher than the viscosity of the pure continuous phase which may affect processability. The potential of confectionery emulsifiers to modulate rheological properties of dispersions has been shown for solid/liquid systems such as chocolate, and for liquid/liquid systems (Chevalley, 1999;Schantz & Rohm, 2005;Sullo et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…1 ) with 40% water (all water droplets below 5 ​μm diameter size) has been suggested to be comparable with normal milk chocolate ( Prosapio and Norton, 2019 ). The use of margarine processing equipment to incorporate water in molten CB could be easily incorporated into chocolate processing plants, and it has been shown to create form V CB crystals ( Sullo et al., 2014 ). Previous work on water-in-CB emulsions showed that shells of sintered CB crystal formed at the oil/water interface, stabilizing the emulsion ( Norton and Fryer, 2012 ).…”
Section: Strategies For Novel Fat Reduced Chocolate Productsmentioning
confidence: 99%
“…Different emulsifiers were also added to further stabilize water-in-CB emulsions. Carrageenan was tested but increasing its concentration past 1.5% w/w led to an increase in unstable CB polymorphs formation, particularly form II ( Sullo et al., 2014 ). The emulsifier soybean lecithin caused flocculation of the water droplets, leading to an increase in chocolate viscosity.…”
Section: Strategies For Novel Fat Reduced Chocolate Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst the material behaviour of hydrocolloids based composite gels and their sensory perception has been investigated in literature (SALA et al, 2007, Sala et al, 2008, there is still a limited number of studies dedicated at understanding the mechanical behaviour of crystallising fats containing emulsified water droplets (Chronakis and Kasapis, 1995, Heertje, 1993, Sullo et al, 2014. To our knowledge, the material properties of these systems and the role played by the dispersed phase have been characterised mainly using small oscillatory rheology (Haj-shafiei et al, 2013, Rafanan andRousseau, 2017).…”
Section: A C C E P T E D Mmentioning
confidence: 99%